Pentalogy of Cantrell with a healthy twin: case report - Tipiani Rodríguez, Oswaldo (2014)
A case of pentalogy of Cantrell pathology in only one fetus of a twin pregnancy is reported; no congenital malformation was found in the second fetus. This fact would endorse epigenetic theories on its origin. Some thoughts on prenatal diagnosis, etiology and management of these cases are discussed.